Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Komitmen Pengurus Serta Implikasinya pada Kinerja Koperasi (Studi pada Koperasi Unit Desa di Jawa Timur) - Djoko Soetjiptadi; Armanu Thoyib; Margono Setiawan; Sucherly - (Jurnal Aplikasi Manajemen, 2012)
This research tried to find the relation among leadership style, organizational culture, commitment, and performance at Village Unit Cooperative in East Java. Specifically, this research aimed at: (1) studying the influence of leadership style and organizational culture to commitment, (2) studying the influence of leadership style and organizational culture to performance, (3) studying the influence of leadership style and organizational culture within commitment to performance. Variables of leadership style are measured using dimensions that are coercive style, authoritative style, affiliative style, democratic style, pacesetting style, and coaching style. Variables of organizational culture are measured using dimensions that are innovation, attention to detail, outcome orientation, people orientation, team orientation, aggressiveness, and stability. While performance variables are measured using dimensions that are vision, capacities, resource, and job network. The result of this research indicates that: (1) leadership style and organizational culture have direct influence that are significant and positive to commitment (2) leadership style and organizational culture have direct influence that are significant and positive to performance, (3) leadership style and organizational culture within commitment have direct influence that are significant and positive to performance. According to the research results that are explained above, the researcher gives the following suggestions: (1) leadership style, organizational culture, and commitment represent variables which need to get special priority to be studied further by future researchers because these variables represent very important elements in taking care of the sustainability of an organization existence at all of level, (2) in order to have a more representative research, the future researchers can add some certain variables, especially moderator variable or intervening variables, that can function as a mediator among leadership style variables, organizational culture, and commitment, (3) the future researches should use more specific analyzer with more modern program, so that there will emerge more research models that are more representative with high level of validity and reliability.Keywords: Leadership style, organizational culture, commitment, and performance